Phyico-chemical investigation of industrial wastewater - Ng, Wei Hong (2011)
This research reviews the physico-chemical investigation of textile industrial wastewater specifically in batik industry. A particular focus is given to physical characteristics, chemical contents and changes for batik industrial wastewater. Initial heavy metals content, heavy metals content during treatment, and heavy metals content after treatment, pH, temperature, and dissolved oxygen are investigated and presented. Beside, the heavy metal contents for flowing industrial wastewater and stagnant industrial wastewater are compared as well. The methodology to investigate the heavy metals content is described from digestion of solution to investigation of specifically heavy metal. 3 heavy metals content were investigated in this research. Among them are Zinc, Manganese, and Aluminium. Two times sampling were done during this research. The reasons to carry out test for these heavy metals content in industrial wastewater will be explain more detail in this research report.